«Херсонский архив печатей»: миф или реальность? - Алексеенко, Н.А. (Херсонесский сборник, 2006)
Появившееся недавно в печати мнение о мифологичности существования как судакского, так и херсонского архивов печатей побудило нас снова обратиться к нашей уникальной находке и попытаться на основе всестороннего анализа ее состава и условий образования комплекса доказать справедливость наших выводов об атрибуции рассматриваемой части херсонских моливдовулов как остатков некого архива документов. Nowadays the number of Cherson’s seals has already exceeded 500 examples; the chronological compass extends the period from the 6th to the 13th A.D. The majority of the seals (about 81 %) covers the 9th-10th A.D. The general group of the town correspondents can be divided into several main groups, including various categories of the clerks of the wide burocratic machine of the Byzantine Empire. The first one includes the delegates of the central state machine: empires, emperial administration and church; the second group consists of the seals of the clerks of the provincial administration and the local tax-financial services; the third group includes the seals of the delegates of the local organs of power (more than150 examples); the last group in the corpus includes the seals, carrying in the monograms or signatures only ranks of their owners. As a rule these seals are the seals of the military and church representatives, the clerks of various departments or the bullae of a private character of the 8th-9th A.D.